Pembelajaran Bilingual English for Health Berbasis Bahasa Ibu Bagi Guru PAUD Kota Semarang - Ririn Ambarini; Eva Ardiana; Dian Ayu Zahraini (Universitas Islam Nahdlatul Ulama Jepara, 2019)
Implementation of Community Service is carried out in the form of training activities, workshops and field assistance which is divided into four stages in a systematic and continuous manner. In phase I, material will be delivered which includes: (1) Social and Emotional Health; (2) Nutrition and Fitness; (3) Safety, first Aid, and Injury Prevention; and (4) Disease Prevention and Control, (5) Techniques for preparing lesson plans on bilingual learning in health and nutrition education for early childhood that can be applied during the teaching and learning process for approximately 30 minutes, at least once a week. Phase II is training in preparing RPP about bullying. Phase III is Peer Teaching Practice and Phase IV is the Discussion and Self-reflection stage. The main aim of this Community Service is that PAUD teachers and staff can implement and implement bilingual learning programs in health and nutrition education in their respective schools so that PAUD teachers and staff can provide healthy living choices while also teaching children to make healthy life choices for them. . The methods used in the implementation of this program include training, lectures, questions and answers, and discussions, teaching practices and worksheets that are the output of participants from this training.